Bobcat : master of survival - Hansen, Kevin (Oxford University Press, 2007)
Foreword by Harley G. Shaw. Introduction. 1. Bobcat Basics. 2. The Petite Predator. 3. From Den to Death. 4. Bobcats at Home. 5. From Predator to Pelt. 6. The Predator Puzzle. Afterword.